2021
DOI: 10.47153/jbmr27.1632021
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Institutional Ownership, Leverage, and Profitability on Firm Value with Dividend Policy as an Intervening Variable

Abstract: The existence of competition requires companies to make various efforts to maintain the existence of the company and increase company value. The company value is indicated by the company's stock price. The purpose of this research is to prove empirically the effect of profitability, leverage and institutional ownership on firm value with dividend policy as an intervening variable. The research data is secondary data in the form of financial statement data and annual reports of companies belonging to the manufa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 4 publications
1
13
1
8
Order By: Relevance
“…The results of this study support the research [12], [13], [14], [15], [16], [17], [18], and [19] who also found that leverage had no effect on firm value. However, the results of this study contradict the research of [4], [5], [6], [7], [8], [9], [10], and [11] that leverage has an effect on firm value.…”
Section: Coefficient Of Determination (R 2 )contrasting
confidence: 99%
See 1 more Smart Citation
“…The results of this study support the research [12], [13], [14], [15], [16], [17], [18], and [19] who also found that leverage had no effect on firm value. However, the results of this study contradict the research of [4], [5], [6], [7], [8], [9], [10], and [11] that leverage has an effect on firm value.…”
Section: Coefficient Of Determination (R 2 )contrasting
confidence: 99%
“…The higher the DER value, the higher the risks faced and have a negative impact on the value of the company. This is in accordance with the research of [4], [5], [6], [7], [8], [9], [10], and [11] that ISSN: 2774-5406 https://ijersc.org leverage has an effect on firm value. Different research results found [12], [13], [14], [15], [16], [17], [18], and [19] that leverage has no effect on firm value.…”
Section: Introductionsupporting
confidence: 90%
“…The authors argued for further work in this regard. In the recent works (Setyabudi, 2021;Salim and Aulia, 2021) the authors reflected in tune with past work and noted the significant associations of profitability, liquidity and leverage with DPO. Yakubu et al (2021) reported a positive causal association among working capital management through cash conversion cycle and days inventory outstanding with DPO based on a study made on a group of non-financial firms in Ghana during 2007 to 2016.…”
Section: Determinants Of Dpomentioning
confidence: 81%
“…The research showed that stock returns can be positively predicted by DPR during the study period (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). In a different study, the researchers observed a moderating effect of the dividend policy on the causal relationship between profitability and value of the firm (Setyabudi, 2021). In the context of Nigeria, Ifeanyichukwu and Yusuf (2021) worked on examining the effect of the share dividends and cash dividend on the market price of the share during the time period 2014-2018.…”
Section: Effect Of Dividend Policy and Dpo On Firm Performancementioning
confidence: 99%
“…Beberapa riset empiris menyatakan bahwa penciptaan nilai pasar perusahaan juga dipengaruhi oleh keputusan keuangan seperti kebijakan dividen (Cristea et al, 2018;Kusumawati et al, 2021;Palupi dan Hendiarto, 2018;Pangaribuan et al, 2019;Margono dan Gantino, 2021;Laksmi dan Budiartha, 2020;Setyabudi, 2021;Setyani, 2018;Soewignyo, 2020;Sucipto dan Sudiyatno, 2018) dan leverage (Cheng dan Tzeng, 2014;Markonah et al, 2020;Margono dan Gantino, 2021;Sari dan Witjaksono, 2021;Sha, 2020). Akan tetapi , berbeda dengan hasil penelitian Nguyen et al (2019) dan Saputri dan Bahri, (2021) yang menyebutkan bahwa kebijakan dividen tidak memiliki pengaruh terhadap penciptaan nilai pasar perusahaan.…”
Section: Pendahuluanunclassified